An assessment of the prevalence and associated burden of symptoms in HIV patients in Swakopmund, Namibia - Brand, Maja (Department of Public Health and Family Medicine, 2016)
Background: HIV infection and AIDS are characterized by a multitude of symptoms which has not changed since the advent of HAART. Based on this reality the World Health Organisation (WHO) recommends palliative care to be provided alongside disease specific treatment for all PLWHIV. There are many barriers to patients reporting their symptoms and physicians often fail to recognise the symptom burden. Palliative medicine improves quality of life, relieves suffering, provides good end of life care and helps patients and loved ones to come to terms with a chronic progressive disease. Namibia is one of the hardest hit countries globally with respect to the HIV epidemic. No palliative care services are available in that country yet. No research has been done to assess the prevalence and burden of symptoms amongst PLWHIV. The study serves as a pilot project to address these shortcomings. Aim: The aim of this study is to assess the prevalence and associated burden of symptoms in patients attending an HIV clinic in Swakopmund and local general practitioners' awareness of the symptom burden and assessment in HIV patients. Methods: This was a cross-sectional descriptive study conducted at the HIV clinic at the State Hospital in Swakopmund, Namibia, and amongst general practitioners working in the Erongo region. The study was conducted in two parts: 1) Assessment of symptom prevalence and severity in HIV patients on HAART attending the HIV clinic at the Swakopmund State Hospital. A total of 104 adult patients were recruited using simple random sampling was used to recruit 104 adult patients who were interviewed using the MSAS-SF. Demographic data and symptoms recorded by the health care professionals during follow-up visits were extracted from the patients' records. 2) The evaluation of general practitioners' perception regarding the symptom burden and importance of symptom assessment in HIV patients receiving HAART. Based on the outcome of the above findings a questionnaire was designed to assess the awareness of general practitioners of the burden of disease in PLWHIV. Ethical Approval was obtained from the Human Research Ethics Committee of the University of Cape Town as well as from the Ethical Committee of the Ministry of Health, Namibia. Results: The median of the sample was 40 years, the median CD4 count 417, and the median number of years on HAART was 4. The majority were females (61.5 %) and 66.3% were employed. The mean number of symptoms was 5.99 (median 5, SD 4.912). The most common symptoms were of psychological nature and pain, cough and peripheral neuropathy were common physical symptoms. Median values of TMSAS, GDI and PSYCH were higher in the unemployed and in females. PHYS was significantly higher in females. There was no association with the CD4 count. Time on treatment is not significantly related to any of TMSAS, GDI, PH YS or PSYCH scores, but younger age was related to higher GDI. Patient self - report of symptoms was significantly higher than symptoms recorded by the health practitioners during follow-up. Many general practitioners (44%) assume patients on HAART to be relatively symptom free, that low CD4 counts are related to symptom burden (84%) and that patients will report symptoms if present(76%). Conclusion: Symptom prevalence and burden is high in this study population despite HAART and there seem to be barriers to the reporting of symptoms by the patients. There is evidence of poor symptom assessment and symptom control. This highlights the need for palliative care for ambulatory HIV patients.